A Novel Surgical Template Design in Staged Dental Implant Rehabilitations - Michael Patras; William Martin; Nikitas Sykaras (Stilus Optimus, 2012)
Background: The philosophy of a gradual transition to an implant retained prosthesis in cases of full-mouth or extensive rehabilitation usually involves a staged treatment concept. In this therapeutic approach, the placement of implants may sometimes be divided into phases. During a subsequent surgical phase of treatment, the pre-existing implants can serve as anchors for the surgical template. Those modified surgical templates help in the precise transferring of restorative information into the surgical field and guide the optimal three-dimensional implant positioning. Methods: This article highlights the rationale of implant-retained surgical templates and illustrates them through the presentation of two clinical cases. The templates are duplicates of the provisional restorations and are secured to the existing implants through the utilization of implant mounts. Results: This template design in such staged procedures provided stability in the surgical field and enhanced the accuracy in implant positioning based upon the planned restoration, thus ensuring predictable treatment outcomes.Conclusions: Successful rehabilitation lies in the correct sequence of surgical and prosthetic procedures. Whenever a staged approach of implant placement is planned, the clinician can effectively use the initially placed implants as anchors for the surgical template during the second phase of implant surgery.